Shared mobility as part of smart urban transport. Analysis of user opinions on the example of the city of Kielce - Pałka, Julia (Developing Sustainable, Smart and Resilient Urban Transportation Systems - Residents’ Perspective, 2024)
The chapter addresses the issue of smart transportation systems and solutions in cities. The starting point for the considerations is the concept of a smart city, where one of the proposed directions for city development is a modern, ICT-based transportation system tailored to the expectations of city users. With technological advancements, various modern transportation solutions emerge, including shared mobility. Digital mobility options in cities are faster, safer, more efficient, and environmentally friendly, and importantly, they complement public transportation and serve as an alternative to individual transport. The aim of the chapter was to identify and assess the implementation of smart city principles in the transportation sector in the city of Kielce, as well as to evaluate the satisfaction of residents and city users with intelligent transportation solutions in the form of shared mobility systems available in the city. The chapter presents the results of a survey conducted among 111 individuals. The study indicates that the majority of respondents are satisfied with the available shared mobility options in Kielce. Younger respondents with medium education levels and high digital competencies demonstrate higher levels of satisfaction.